Effect of real particles packing with large size ratio on porosity and tortuosity of filter bed - Mota, M. (2004)
The complexity of processes involved in the formation of granular beds results in limited information about permeability κ , which directly rela tes with packing porosity ε and tortuosity T . For a mixed bed of particles significantly different in size, the influence of packing affects permeability. For a better understanding of the underlying relationship between κ , ε , and T in mixed beds of particles significantly different in size, simplified porous media model of binary mixture of spheres were used. Boundary analysis of the binary packing showed that the approach based on the fractional porosity of large and small size particle fractions gives a tool for ε control. This approach allows a new insight into the mixture structure and provides explanation for the different types of the obtained porosity. Binary packing of glass beads with size ratios 13.3, 20, and 26.7 were investigated. As a basic relation for the dependence of T on ε, at different volume fraction xD of large particles in the mixture, the formula T=1/ εⁿ was used. The obtained experimental results show that the parameter n is a function of the packing content xD and may vary in the range of 0.4-0.5. The reason for n variation was explained by the wall effect of the small particles arrangement occurring near the large particles surface. A model accounting for this effect is proposed and may be useful for transport phenomena analysis in granular bed filters.